Synthesis, Docking, and Biological Studies of Pyrazine Derivatives as Antimycobacterial Agents - Gangarapu, Nagaraja Reddy; Ranganatham, Archakam; Reddy, Eeda Koti; Kumar, Chakka Kiran; Yellappa, Shivaraj; Chandrasekhar, Kothapalli Bannoth; Manickan, Elanchezhiyan (Medicinal Chemistry, 2025)
IntroductionA series of novel 2-((3,5-diphenylpyrazin-2-yl)amino)-1-(piperidin-1-yl/pyrrolidin-1-yl)ethanone derivatives (5a-5l) were synthesized and evaluated for their tuberculosis activity using the standard strain H37Rv and two other clinically isolated multidrug-resistant strains with different resistances.MethodsAll compounds 5a-5l showed promising results in tuberculosis activity. Among them, 5g and 5i demonstrated remarkable activity at 5 μg/mL against H37Rv and three other MDR strains. The compounds 5c, 5d, and 5f were sensitive, showing inhibition between 15-25 μg/mL against M. tuberculosis growth. In-silico docking studies were conducted for 5a-5l using the 2FUM protein of M. tuberculosis.ResultsThese studies revealed that compounds 5g and 5i exhibited strong interactions with the MTB protein, with binding energies of -9.85 kcal/mol and -10.74 kcal/mol, respectively, and inhibitory concentrations of 0.38 µM and 0.77 µM.ConclusionMoreover, these motifs also displayed good binding energy coupled with favorable minimum inhibitory concentrations (MIC).
Keywords: H37Rv